Deteksi DNA Spesies pada Produk Makanan Olahan Daging Ayam Menggunakan Gen GH (Growth Hormone) sebagai Penanda Molekuler - Sophian, Alfi; Utaminingsih, Sri; Yenita, Yenita; Purwaningsih, Ratna (Food Scientia : Journal of Food Science and Technology, 2024)
The species DNA detection test in processed chicken meat food products using genetic growth hormone (GH) gene markers is a novel approach for authenticity test regarding the presence of a particular species in a product. This research aimed to test the ability of the GH genetic marker to detect the presence of chicken species in processed chicken meat food products. The method used in this research is a molecular biology method using real-time PCR with the SYBR Green kit. The genetic marker primers used were designed independently from the NCBI website. Based on DNA isolation data, the DNA concentration value is 43.60 ng/µL – 45.20 ng/µL with an average of 44.11. The purity value of isolated DNA is 1.855 – 1.925 with an average of 1.906. Chicken species DNA was detected in all samples using real-time PCR analysis, with a Ct value of 24.50 and a Tm value of 78.10. However, the Ct and Tm values were not detected in the negative control (NTC) and specificity (internal) control samples. In the positive control LOD, the Ct value was detected at 27.20 with a Tm value of 79.40. In the positive control, a Ct value of 21.10 and a Tm value of 78.10 were detected. The results indicate that all samples contained the GH gene, and hence, chicken species DNA was detected in all samples. This suggests that the GH genetic marker can be potentially used for species DNA identification testing.